Analyzing discrepancies between willingness to pay and willingness to accept for freight transport attributes. (May 2016) - Feo-Valero, María; Arencibia, Ana Isabel; Román, Concepción
Highlights: We analyze the asymmetric perception of freight transport attributes. We considered a reference dependent utility specification. We analyze discrepancies between WTP and WTA for freight transport attributes. We estimate choice models in both preference and WTP and WAT space. Results are useful to evaluate alternative services to road transport. Abstract: In this paper we use discrete choice data to analyze asymmetries in the preference for freight transport attributes. A reference dependent utility specification allowed us to test for the existence of substantial asymmetries in perception of the transport cost. Hence, the re-estimation of our models in the WTP/WTA space helped us to quantify significant discrepancies between the WTP and WTA for the attributes included in the choice experiment, namely transit time, service frequency and delays in delivery time. Results are deemed essential to define alternative services to road capable to attract substantial volumes of freight.